The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1007/s10561-008-9103-2
|View full text |Cite
|
Sign up to set email alerts
|

Quality control of cultured tissues requires tools for quantitative analyses of heterogeneous features developed in manufacturing process

Abstract: Tissue engineering and related technology have attracted a great deal of medical attention as promising fields for curing defective tissues in vivo. Nowadays, many companies have been established for supplying the reconstructed grafts of cultured tissues for transplantation. The manufacturing processes generally deals with the handlings of starter cells offered by patients (or donors) as raw materials to cultured tissues as products, requiring the construction of novel ex vivo methodologies based on principles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2009
2009

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 68 publications
0
1
0
Order By: Relevance
“…Confocal microscopy is beginning to establish itself as a method of examining tissues in vivo as a diagnostic tool for the human cornea [6,7] and for skin [8,9]. This technique has also been examined for in vitro quality control of tissue engineered constructs [10,11]. It has been suggested that collagen plays an important role in the maximum load force of tissue-engineered constructs [12-14].…”
Section: Introductionmentioning
confidence: 99%
“…Confocal microscopy is beginning to establish itself as a method of examining tissues in vivo as a diagnostic tool for the human cornea [6,7] and for skin [8,9]. This technique has also been examined for in vitro quality control of tissue engineered constructs [10,11]. It has been suggested that collagen plays an important role in the maximum load force of tissue-engineered constructs [12-14].…”
Section: Introductionmentioning
confidence: 99%